Quantifying e-governance efficacy towards Indian–EU strategic dialogue. Issue 4 (16th October 2017) - Soni, Vivek; Anand, Rashmi; Dey, Prasanta Kumar; Dash, Ambika Prasad; Banwet, Devinder Kumar
Abstract : Purpose: The purpose of this research paper is to assess efficacy of e-governance implementation, influenced under the Indian-EU (European Union – EU) strategic dialogue. For the same purpose, this study aims to analyse and measure penetration level of information and communication technology (ICT) applications across ten select gross domestic product-dependent sectors (gross domestic product – GDP) in Indian economy. Design/methodology/approach: Multi-criteria decision-making (MCDM) approach of PROMETHEE, using its partial and complete versions in fuzzy environment, is applied. The approach assesses e-governance efficacy in various sectors, which is chosen based on their contribution to GDP, where criteria values are assigned by expert opinions, feedback is received and lessons are learnt from training and initiatives taken under the Digital India programme launched by the Government of India. These criteria related to IT policy implementation, cyber security breaches, IT infrastructure development initiatives in select sectors are identified. Later, sectors outranking results have been highlighted using both fuzzy set theory along with PROMETHEE (F-PROMETHEE) and its visual application. Findings: On applying F-PROMETHEE, studies found that industrial, railways, health and finance and education sectors outrank in their high merit orders. Contrary, outranking shows that agriculture, defence and aerospace sectors should be more open and accessible to adopt ICT applications in order to promote e-governance processes and their implementation to make e-services available to common citizens. For better interpretation of results, graphical analysis for interactive aid is used to present the analyses. Research limitations/implications: Research study was found useful in the assessment of ICT penetration level in to support Indo-EU relations, where PROMETHEE method is used to outrank sectors alternatives. Criteria are also weighted using fuzzy scale, and the impact of criteria on all alternatives has also been assessed. MCDM framework addresses that subjectivity lies in sectors to implement ICTs bases services. However, few other MCDM frameworks, methods such as COPRAS, GST, GRA, SAW and SWARA, can be used for the same purpose. Practical implications: Sectors alternative involve high degree of complexity to adopt ICT applications for smooth e-governance and seek effective decision-making for investment prioritization and future development. This study also aims to address cyber security concerns of policymakers. Outranking methods of F-PROMETHEE are able to address the criteria-to-criteria impact and support decision-making in a more precise way. Social implications: This study is inspired from the strategic implementation of the framework of the e-Government Action Plan 2016-2020 of the EU. The findings from the paper can provide referential support to the Indian Government and policymakers to support information delivery, implement cyber security policies and various sector developments. Originality/value: This research study can act as a strong base in the decision-making process in conflicting situations of e-governance in India. This study not only can synergize conflicting ideas of various stakeholders, academicians in the Indian IT-sector but also can act as support to administrators and the policymakers to monitor the status of the India-EU Information Society Dialogue.